Manutenção de tensão em transitórios de carga : análise de uma microrrede com aerogerador e armazenamento em baterias - Barzola Iza, Jhonny Javier (2016)
Distributed generation, incorporated or integrated, consists of isolated generating units connected through the supply system of less power than the concentrated generation of large power plants. The so-called microsources are, in turn, sources of electric power of much less power relative to the distribution network where they are connected. From these sources, such as photovoltaic panels, small wind power systems, fuel cells, microturbines and others, that are located near the loads, consumers can generate their own electricity and even supply the surplus to the distribution network of its location. To connect a microsource in the local distribution network, this must be in synchronism with the main network. Therefore, it is necessary that the differences in voltage, frequency and phase are negligible and thus avoid destabilizing the system. In wind turbines, the power output level at each time is uncertain because of the variable wind. This may cause instability in the system when working autonomously. This is where energy storage systems are a good proposal to reduce these variations, even for getting a steady flow of power. This dissertation analyzes the modeling and simulation in PSCAD of a wind turbine with a permanent magnet synchronous generator connected to a network through a controlled converter in power and voltage. It also considers the inclusion of an energy storage system based on batteries, to show the wind turbine behavior during wind and load variations, with and without the attached storage system. The storage system seeks to maintain constant power flow to the network. The results show the utility of the approach.